ANSYS Creep-Fatigue Assessment tool for EUROFER97 components. (December 2016) - Mahler, M.; Özkan, F.; Aktaa, J.
Highlights: Creep-Fatigue Assessment (CFA) tool to identify EUROFER97 damage of complex 3D geometry. CFA tool based on creep-fatigue rules of ASME BPVC. Integrated in ANSYS MAPDL and Workbench as a post-processing tool. Identification of the most critical region in the component. Abstract: The damage caused by creep-fatigue is an important factor for materials at high temperatures. For in-vessel components of fusion reactors the material EUROFER97 is a candidate for structural application where it is subjected to irradiation and cyclic thermo-mechanical loads. To be able to evaluate fusion reactor components reliably, creep-fatigue damage has to be taken into account. In the frame of Engineering Data and Design Integration (EDDI) in EUROfusion Technology Work Programme rapid and easy design evaluation is very important to predict the critical regions under typical fusion reactor loading conditions. The presented Creep-Fatigue Assessment (CFA) tool is based on the creep-fatigue rules in ASME Boiler Pressure Vessel Code (BPVC) Section 3 Division 1 Subsection NH which was adapted to the material EUROFER97 and developed for ANSYS. The CFA tool uses the local stress, maximum elastic strain range and temperature from the elastic analysis of the component performed with ANSYS. For the assessment design fatigue and stress to rupture curves of EUROFER97 as well as isochronous stress vs. strain curves determined by a constitutive model considering irradiation influence are used to deal with creep-fatigue damage. As a result allowable number of cycles based on creep-fatigue damage interaction under given hold times and irradiation rates is obtained. This tool can be coupled with ANSYS MAPDL and ANSYS Workbench utilizing MAPDL script files.